2023
DOI: 10.3390/toxics11070596
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation Pattern and Health Risk Assessment of Heavy Metals in Cirrhinus mrigala at Panjnad Headworks, Bahawalpur, Pakistan

Abstract: Heavy metal accumulation in freshwater ecosystem has become one of the major aquatic environmental concerns for freshwater flora and fauna due to their higher stability and bioaccumulation as well as bio-magnification properties. Furthermore, passing through the food web, these heavy metals affect human populations ultimately. This study assessed the heavy metal accumulation in Cirrhinus mrigala in spring, autumn, and winter at different locations (I, II, and III) of Panjnad headwork. Furthermore, the human he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
3
1
Order By: Relevance
“…The result of our findings is incompatible with [27,28] and [29]. The findings revealed that the concentrations of two metals (Cr, Ni) were notably higher in farm-raised rohu in comparison to wild rohu.…”
Section: Bioaccumulation Of Heavy Metalscontrasting
confidence: 95%
“…The result of our findings is incompatible with [27,28] and [29]. The findings revealed that the concentrations of two metals (Cr, Ni) were notably higher in farm-raised rohu in comparison to wild rohu.…”
Section: Bioaccumulation Of Heavy Metalscontrasting
confidence: 95%
“…In our research, we observed significant alterations in hematological and biochemical parameters, consistent with previous reports. The potential release of cadmium chloride into aquatic ecosystems raises specific concerns, especially in light of research demonstrating its high toxicity to various freshwater aquatic species (Lee et al, 2007;Asharani et al, 2008;Griffitt et al, 2008;Naz et al, 2023b).…”
Section: Serum Biochemical Parametermentioning
confidence: 99%
“…As these metals swiftly integrate into the aquatic environment, they become a part of the food chain, affecting both aquatic organisms and human populations reliant on them (Chatha et al, 2023). At present, the problem of aquatic pollution has increased many times due to the introduction of modern technologies using heavy metals as raw materials for different functions (Naz et al, 2023b).…”
mentioning
confidence: 99%
“…Heavy metals are elements that cannot be decomposed (persistent) and can accumulate through the food chain (bioaccumulation), with long-term detrimental effects on living things [6]. At low concentrations, heavy metals can disrupt physiological or metabolic processes and cause damage to animal organs [7][8].…”
Section: Introductionmentioning
confidence: 99%